Age and growth of Antarctic deep-sea smelt (Bathylagus antarcticus), an important mesopelagic fish in the Southern Ocean. (July 2022) - Liu, Chunlin; Zhang, Chi; Liu, Yang; Ye, Zhenjiang; Zhang, Jie; Duan, Mi; Tian, Yongjun
Abstract: As one of the most abundant mesopelagic fishes, the Antarctic deep-sea smelt Bathylagus antarcticus plays an important role in the Southern Ocean ecosystem. However, because of a lack of studies on this species, there are major gaps in our knowledge of its life history such as age and growth pattern. Fish were collected from the Ross and Amundsen seas in the southern part of the Pacific sector, and from the Cosmonaut Sea in the southwestern part of the Indian sector, in austral summer of 2020. Age determination was made from an analysis of otoliths, and growth curves were estimated through mixed-effects models based on back-calculated length-at-age data. Bathylagus antarcticus shows a positive allometric relationship between total length and wet weight; the results indicate that it can live to age 17 years; and the von Bertalanffy growth function was estimated on the population level with L ∞  = 143.83 mm, K  = 0.14 year −1, and t 0  = −0.64 year. Fish in the Ross and Amundsen seas showed larger mean asymptotic length than that fish in the Cosmonaut Sea, and the K values and otolith growth increments in the first 6 years differed between regions. This work is the first to estimate the age and growth of B. antarcticus, and forms an important basis of forthcoming studies on population dynamics and ecosystems in the Southern Ocean. The long lifespan and slow growth of this species make it a potentially suitable environmental indicator, to be investigated through tools like otolith microchemistry analysis.